Phlebotomine sandfly fauna (Diptera: Psychodidae) of Falcon state, Venezuela - Cazorla, Dalmiro J. (2012)
Composition, abundance and dispersion of phlebotomine sandfly fauna were studied in Falcon state, Venezuelan north-western region. The sandflies were collected by five methods in 41 localities between 0 to 1584 m. A total of 6273 specimens were collected, 17 species of Lutzomyia and 1 of Brumptomyia were identified. Of these, 10(55.56%) species are known to be anthropophilic. The predominant species was L. evansi (52.37%). The diversity and dispersion range of sandflies along an altitudinal transect, are presented. The significance of sandfly fauna in the transmission of leishmaniases in the Falcon state region is discussed.